The biographical adventure in Hanna Minh's novels - سمير ذياب سلمان البديري, الباحث (lark, 2021)
The novelist created his own specialty in writing fictional texts, so biographical texts were formed in novels, to be among the successful innovative adventures that were unique to the novelist. This novelistic technique made the writer’s novels bear a different characteristic that represents the extension of the writer’s biography in the novels that are at the origin of their subject matter that do not represent the writer and do not represent his biography, except that by including biographical texts that bear conformity to the reality of his life and events, which he formulated with artistic realism, he carried The reader is led to believe that all of these novels and the events that take place in them are a realistic representation of the writer's life. Thus, the biographical texts have succeeded in their adventure by deluding the reader with the reality of events in multiple narrations.